Antioxidant Effects of Schisandra chinensis Fruits and Their Active Constituents - Kopustinskiene, Dalia M. (Antioxidants (Basel), 2021)
Schisandra chinensis Turcz. (Baill.) fruits, their extracts, and bioactive compounds are used in alternative medicine as adaptogens and ergogens protecting against numerous neurological, cardiovascular, gastrointestinal, liver, and skin disorders. S. chinensis fruit extracts and their active compounds are potent antioxidants and mitoprotectors exerting anti-inflammatory, antiviral, anticancer, and anti-aging effects. S. chinensis polyphenolic compounds—flavonoids, phenolic acids and the major constituents dibenzocyclooctadiene lignans are responsible for the S. chinensis antioxidant activities. This review will focus on the direct and indirect antioxidant effects of S. chinensis fruit extract and its bioactive compounds in the cells during normal and pathological conditions.